Edukasi Kesehatan Reproduksi Calon Pengantin Terhadap Pengetahuan dan Keikutsertaan Premarital Check Up - Melati Puspita Sari; Ernawati Anggraeni (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Education on reproductive health is very important to be given to prospective brides, especially couples who are about to get married. The lack of knowledge of prospective brides about reproductive health and premarital check-ups leads to low participation in premarital check-ups. KUA Kaliwates is a KUA that does not run guidance programs and courses for prospective brides due to limited DIPA funds from the Ministry of Religious Affairs of Jember Regency. The purpose of this study was to determine the effect of reproductive health education of prospective brides on knowledge and behavior of participation in premarital check-ups. The research conducted was a quasi-experimental with a one group pretest-posttest. Accidental sampling is all prospective brides in the Kaliwates KUA working area in June-July 2022 totaling 49 prospective brides. McNemar test shows the value (p value = 0.008) Î± < 0.05 means that there is an effectiveness of reproductive health education of prospective brides on knowledge and the value (p value = 0.016) Î± < 0.05 means that there is an effectiveness of reproductive health education of prospective brides on the participation of premarital check up.